Effect of torso morphology on maximum hydrodynamic resistance in front crawl swimming - Papic, C.; McCabe, C.; Gonjo, T.; Sanders, R. (Sports Biomechanics, 2020)
The aim of this study was to determine the influence of torso morphology on maximum instantaneous hydrodynamic resistance in front crawl swimming. Outlines of the torso in the frontal and anteroposterior planes were calculated from photographic images to determine continuous form gradients (m/m) for the anterior, posterior and lateral aspects of the torso. Torso cross-sectional areas at each vertical sample (0.001 m) were used to calculate maximal rate of change in cross-sectional area (m2/m) in the chest-waist and waist-hip segments. During the non-propulsive hand phase in middle-long distance front crawl, kicking propulsion is negligible and therefore the net force is equal to the drag. Drag coefficients were calculated at the instant of maximum horizontal deceleration of centre of mass during the non-propulsive hand phase of 400 m pace front crawl. Maximal rate of change in cross-sectional area (r = 0.44, p = 0.014) and posterior form gradient (r = 0.50, p = 0.006) of the waist-hip torso segment had moderate positive correlations with the maximal drag coefficient. A regression model including these variables explained 41% of the variance (p = 0.001). Indentation at the waist and curvature of the buttocks may result in greater drag force and influence swimming performance.